Factors Associated With The Nutritional Status Of Preschool Children - Popy Andini; Rohaya Rohaya; Helni Anggraini (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2022)
Latar Belakang: Status gizi adalah keadaan tubuh yang mengakibatkan makanan yang dikonsumsi dan penggunaan gizi yang baik diperoleh dari pola makan yang seimbang, yang akan berdampak pada pertumbuhan fisik, perkembangan otak, dan kesehatan anak. Status gizi yang tidak seimbang akan memberikan pengaruh yang berbahaya bagi tubuh, yaitu dapat menimbulkan efek toksik. Di Indonesia, prevalensi status gizi balita dilihat dari indeks berat badan menurut umur (BB/A) diketahui mengalami gizi kurang sebesar 3,9%, gizi kurang 13,8%, gizi baik 79,2%, dan gizi lebih. sebesar 3,1%.Tujuan: untuk mengetahui hubungan pendidikan ibu, pola makan balita, dan riwayat penyakit balita dengan status gizi balita di Desa Karya Mukti Kecamatan Sinar Peninjauan Kabupaten OKU Kabupaten OKU. 2021.Metode: Desain penelitian kuantitatif, dengan metode survei analitik melalui pendekatan cross sectional. Populasi adalah seluruh ibu dengan anak usia 4-5 tahun di Desa Karya Mukti Kecamatan Sinar Peninjauan Kabupaten OKU periode Juni 2021 berjumlah 35 balita. Teknik pengambilan sampel dalam penelitian ini adalah total sampling. Kemudian, analisis data univariat dan bivariat dan uji statistik Chi-SquareHasil: Dari uji statistik Chi-Square pada variabel pendidikan ibu didapatkan nilai p-value 0,001 (< = 0,05), dan variabel pola makan anak didapatkan nilai p-value 0,003 (< = 0,05). Hal ini menunjukkan adanya hubungan yang signifikan antara pendidikan ibu, pola makan anak, dan status gizi anak prasekolah di Desa Karya Mukti. Sedangkan riwayat penyakit pada balita memiliki p-value sebesar 0,221 (< = 0,05).Kesimpulannya, tidak ditemukan hubungan yang signifikan antara riwayat penyakit dengan status gizi anak prasekolah di Desa Karya Mukti.Saran: Kepada Desa Karya Mukti disarankan untuk lebih aktif memberikan penyuluhan kepada ahli kebidanan tentang status gizi anak prasekolah. Kata kunci: Pendidikan, Diet, Riwayat Penyakit, Status Gizi ABSTRACT Background: Nutritional status is a condition of the body that results in the food consumed and the use of good nutrition obtained from a well-balanced diet, which will impact children's physical growth, brain development, and health. An unbalanced nutritional status will have a dangerous influence on the body, which can cause toxic effects. In Indonesia, the prevalence of nutritional status of children under five, as seen from the weight index for age (W/A), revealed that they suffered from malnutrition by 3.9%, undernutrition by 13.8%, good nutrition by 79.2%, and overnutrition by 3.1%.Objectives: This study aims to determine the relationship between mothers’ education, children under-fives diet, and children under-fives history of illness and the nutritional status of preschool children in Karya Mukti Village, Sinar Peninjauan Sub-district, OKU Regency, in 2021.Method: This study’s design was quantitative, with an analytical survey method through a cross-sectional approach. The population was all mothers with children aged 4-5 years in Karya Mukti Village, Sinar Peninjauan Sub-district, OKU Regency, for the period of June 2021, totaling 35 children under five. The sampling technique in this research was total sampling. Then, the univariate and bivariate data analyses and Chi-Square statistical tests were employed.Results: From the Chi-Square statistical test on the mothers’ education variable obtained a p-value of 0.001 (< α = 0.05), and the children’s diet variable got a p-value of 0.003 (< α = 0.05). It denotes a significant relationship between mothers’ education, children’s diet, and the nutritional status of preschool children in Karya Mukti Village. Meanwhile, the history of illness in children under-five had a p-value of 0.221 (< α = 0.05). In conclusion, no significant relationship was found between the history of illness and the nutritional status of preschool children in Karya Mukti Village.Suggestions: The Karya Mukti Village is advised to be more active in providing counseling to midwifery experts on the nutritional status of preschool children. Keywords: Education, Diet, History of Illness, Nutritional Status